Quantitative Association Between Serum/Dietary Magnesium and Cardiovascular Disease/Coronary Heart Disease Risk: A Dose–Response Meta-analysis of Prospective Cohort Studies. Issue 6 (December 2019) - Zhao, Lingyun; Hu, Meng; Yang, Lei; Xu, Haoming; Song, Wenyan; Qian, Yazhi; Zhao, Meimi
Abstract : Background: The quantitative association between serum/dietary magnesium and cardiovascular disease (CVD) remains unclear. We conducted a dose–response meta-analysis to evaluate the quantitative association between serum/dietary magnesium and CVD, including coronary heart disease (CHD). Methods: PubMed, China National Knowledge Infrastructure, and Web of Science were searched for publications. STATA 12.0 was used to analyze data. We used the random-effects model to reduce heterogeneity. Results: Eighteen prospective cohort studies with 544, 581 participants and 22, 658 CVD cases were included. The follow-up duration was 1–28 years. The pooled relative risk (RR) of CVD for the relatively normal versus lowest serum and dietary magnesium level was 0.64 {[95% confidence interval (CI): 0.51–0.80] and 0.90 [95% CI: 0.84–0.96]}. The pooled RR of CHD for the relatively normal versus lowest serum and dietary magnesium level was 0.70 (95% CI: 0.57–0.85) and 0.86 (95% CI: 0.77–0.94). We noted a significant association between increasing serum magnesium levels (per 0.1-mg/dL increase) and risk of CVD (RR: 0.93, 95% CI: 0.88–0.97) and CHD (RR: 0.90, 95% CI: 0.84–0.96) and between dietary magnesium levels (per 100-mg/d increase) and risk of CVD (RR: 0.90, 95% CI: 0.83–0.96) and CHD (RR: 0.92, 95% CI: 0.82–0.98). Serum/dietary Mg level comparisons presented a 7%–10% decrease in CVD/CHD risk. The dose–response meta-analyses showed linear relationships between serum magnesium and CVD (Pnonlinearity = 0.833) or CHD (Pnonlinearity = 0.193) and dietary magnesium and CVD (Pnonlinearity = 0.463) or CHD (Pnonlinearity = 0.440). Conclusions: Increasing dietary magnesium or serum magnesium level is linearly and inversely associated with the risk of total CVD and CHD events.